War and Its Impact on the Reconstruction of the Naval Potential of the Polish People’s Republic after 1945 - Drzewiecki, Andrzej (Social consequences of war, 2024)
When it comes to naval potential, we must have at least two dimensions in mind. The one is the social potential identified with the personnel (naval) structures and civilian personnel and their qualifications, while the other is the combat potential expressed in the state of armaments and equipment of the naval forces. There is no doubt that in 1945 Poland faced the necessity of building the naval component of the armed forces, not from scratch but with numerous limitations. We dealt here with internal limitations caused by the aftermath of the war and external ones due to the fact that Poland came under the Soviet sphere of influence, which had a direct bearing on the scope of independence in the military field. This subordination and its consequences were experienced to the full extent by the navy, which undoubtedly translated into its potential and operational independence.